Factors affecting the uptake of insurance products in the banking sector between 2013 and 2018: Case of First Capital Bank, Zimbabwe (International Journal of Scientific Research and Management (IJSRM), 2022)
The research paper evaluated the factors affecting the uptake of insurance products in the Zimbabwean banking sector. Case study of First Capital Bank (FCB) was used. The main objective of the study is to analyse the factors affecting the uptake of insurance products. The study adopted a mixed methods research design and a pragmatism research philosophy. The population was made up of 312 employees and 150 000 customers making a total population size of 150312.Qquestionnaires and interviews were used to collect data. The research findings were that customers are well aware of the endowment policy, term insurance and the whole insurance product available at FCB. In addition, the research found out that customers have limited choice in terms of the uptake of insurance policies of their choice at FCB. It was noted that there has not been an increase in the rate of consumption of insurance. The study concluded that FCB has insurance policies and uptake of insurance at FCB was low. The study concluded that economic and political factors and socio-cultural factors affect the uptake of insurance services by the people at FCB. The study recommended that bank should offer new products to the existing and should also increase its service range by offering other types of insurance services like motor vehicle insurance.